Learning from failure feedback for subsequent task performance: A matter of personality? - Thiel, Katharina; Semrau, Thorsten (Frontiers in Psychology, 2022)
The present study expands our knowledge of the differential consequences of failure feedback. Specifically, we conducted an online experiment to elaborate on how conscientiousness and extraversion contribute to explaining whether individuals learn from failure feedback for future task performance. In line with our hypotheses, we find that individuals who are highly conscientious and/or highly extraverted are more likely to learn from failure feedback than their counterparts. We discuss the implications of our study and derive practical implications.